Saudi-led Arab coalition’s military intervention in Yemen from the international law perspective - Mohammad Reza Pourbehi, Mohammad Ali Kazemi (Opción, 2019)
The present study aims to examine the military intervention in Yemen from the perspective of international law through the cross-case comparisons research method. As a result, the illegitimate Arab coalition invasion of the independent Yemeni state violated numerous international humanitarian rules, including attacking civilians and civilian sites. As a conclusion, the use of prohibited weapons against the Yemeni people, including chemical weapons and cluster bombs, is also among the other war crimes in this crisis. These examples provide solid evidence for human rights violations and the commission of war crimes in Yemen's armed conflic